Folding of protein secondary structures using a novel polarizable force field method - Yip, Yew Mun (2017)
Protein folding is a complicated process that bridges the understanding between the protein structure and its biological function. The “protein folding problem” is continuously being pursued in the protein community up till today and there have been many principal studies conducted to comprehend protein folding. While numerous experimental efforts have been devised to probe the understanding of the protein folding process, these methods faced limitations. With technology advancing rapidly, the MD simulation is becoming an essential tool to understand the protein folding process dynamically at the atomic level. Modelling of the exact nature of these interactions makes theoretical prediction of native structures a complex task as the correctness of the prediction depends heavily on the quality of the force field used. However, the absence of the polarization effect in force fields has reduced the accuracy of MD simulations when studying protein folding. Therefore, we developed a novel atomic charge update method known as the Polarized Structure-specific Backbone Charge (PSBC) model. The PSBC model accounts for polarizability by periodically updating the charges of atoms involved in backbone hydrogen bonding during the MD simulation. In addition, the model does not employ computationally expensive quantum-mechanical calculations on-the-fly during MD simulations. The model is applied to peptides of various challenging secondary structures to rigorously test its capability, effectiveness and accuracy.